Variabilidade das chuvas na vertente Paranaense da bacia do rio Paranapanema - 1999-2000 a 2009-2010 - Carmello, Vinicius [UNESP]; Sant'Anna Neto, João Lima [UNESP] (My University, 2015)
Investments in agriculture have been expanded during the past decades, especially to minimize the impact, said natural in the agricultural territory occupied. This paper aims to analyze the rainfall variability in the slope of Paranapanema river basin, Paraná state during the soybean crop (October-April). To target this, two statistical techniques were applied: Mann-Kendall and Percentile, to analyze the trend and the total annual rainfall variability between: 1999-2000 to 2009-2010. Are used precipitation data from 89 stations administered by Instituto das Água do Paraná and was defined extremely dry, dry, normal, rainy and extremely rainy periods, represented in a panel time-space. The Mann-Kendall test showed 13 stations with positive trend of increased rainfall. Regarding related to variability in annual rainfall accumulated more significant results, it was concluded that the agricultural year 1999-2000 was defined as dry pattern, in contrast to the rainy year 2009-2010. The soybeans data presented to measure these extreme periods impacts also fluctuated in relation to precipitation for each year.
Raifall variability on the slope of Paranapanema river basin, Paraná state - 1999-2000 to 2009-2010
Keywords: Agriculture; Climate; Impact; Paraná; Rainfall; Soybean